Konstruksi Sosial Stigma terhadap Mahasiswa Penyandang Disabilitas di Fakultas Ilmu Pendidikan: Analisis Perspektif Erving Goffman - Rahmi R, Nurazizah; Bastiana, Bastiana; Zulfitrah, Zulfitrah; Nurul Mutahara B; Wizerti Ariastuti Saleh (CV. ULIL ALBAB CORP, 2025)
This study examines the social construction of stigma toward students with disabilities in the Faculty of Education at Universitas Negeri Makassar through Erving Goffman's theoretical perspective. The research aims to understand how stigma is constructed and manifested in the academic environment, particularly focusing on students' attitudes and perceptions. Using a descriptive quantitative approach, data were collected through a structured questionnaire administered to 40 students from various semesters (2nd to 9th) in the Faculty of Education. The questionnaire consisted of 33 items measuring different dimensions of stigma, including character stigma, courtesy stigma, and impression management strategies. Results indicate varying levels of stigma manifestation among students, with notable patterns in academic perception, social interaction, and disclosure attitudes. The findings reveal that while students generally show positive attitudes toward inclusion, subtle forms of stigma persist in social interactions and academic expectations. This study contributes to understanding disability stigma in higher education contexts and provides insights for developing more inclusive educational environments. The research implications suggest the need for comprehensive disability awareness programs and institutional policy reforms to address stigma-related barriers in academic settings.